2018
DOI: 10.1016/j.biortech.2018.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of torrefaction pretreatment on the pyrolysis of rubber wood sawdust analyzed by Py-GC/MS

Abstract: The aim of this study was to investigate the effect of torrefaction on the pyrolysis of rubber wood sawdust (RWS) using pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). Three typical torrefaction temperatures (200, 250, and 300 °C) and pyrolysis temperatures (450, 500, and 550 °C) were considered. The results suggested that only diethyl phthalate, belonging to esters, was detected at the torrefaction temperatures of 200 and 250 °C, revealing hemicellulose degradation. With the torrefaction temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Chen et al researched the effect of torrefaction pretreatment on the pyrolysis of rubber wood sawdust through pyrolysis-gas chromatography/mass spectrometry and concluded that the contents of oxy-compounds, such as acids and aldehydes, decreased with rising torrefaction temperature [74]. Finally, in [86], the effects of torrefaction on physical properties, chemical composition, and reactivity of microalgae were studied.…”
Section: Future Perspectives and Research Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al researched the effect of torrefaction pretreatment on the pyrolysis of rubber wood sawdust through pyrolysis-gas chromatography/mass spectrometry and concluded that the contents of oxy-compounds, such as acids and aldehydes, decreased with rising torrefaction temperature [74]. Finally, in [86], the effects of torrefaction on physical properties, chemical composition, and reactivity of microalgae were studied.…”
Section: Future Perspectives and Research Developmentsmentioning
confidence: 99%
“…The torrefaction of biomass has been attracting a considerable amount of attention in the research community in the last few years [27,[74][75][76][77][78]. Thus, the authors proceeded to the quantification of this interest.…”
Section: Research Focused On Torrefactionmentioning
confidence: 99%
“…Some food additive and aroma substances were found in C. For example, 2-Methoxy-4-vinylphenol (4.08%), Phenol, 2,6-dimethoxy-4-(2-propenyl) - (2.34%) and n-Hexadecanoic acid (1.74%). N-Hexadecanoic acid has special aroma and taste, which can be used to prepare various edible flavors, defoamers and other food additive (Chen et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…0.010 g of CCB extracts were placed in the cracking tube, with glass wool in the cracking device sampler. The pyrolysis conditions are as follows: 50 °C, 1 sec standing time, 20 °C/MS flow rate, 700 °C or 550 °C flow rate, hold for 10 s. Interface conditions: 80 °C, flow rate 100 °C/min to 300 °C, keep 2 min (Chen et al, 2018). Valve furnace: 300 °C, transmission line: alpha C, GC–MS./MS conditions: HP-5 capillary column (30 m × 0.25 mm × 0.25 µm); carrier gas, helium, carrier gas flow, 1 mL/min, injection volume, 1 °C, 29 sample injection temperature: 280 °C, split ratio 5:1 (Almeida et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 and Figure A2 (in Appendix A) show the relative mass contents of sawdust torrefied in the vacuum and the nitrogen systems at 300 • C for 60 min. The liquid products were largely composed of condensable components such as phenols, acids, alcohols, aldehydes, and ketones (see Table 3) [43][44][45]. All of the results reported in Table 3 are mutually comparable because they were obtained under the same operating conditions as programed in the MS instrument.…”
Section: Gc/ms Analysis Of Liquid Compoundsmentioning
confidence: 86%